Some problems of data security of digital tachograph system - Nowacki, Gabriel; Mitraszewska, Izabella; Wojcechowski, Andrzej; Kamiński, Tomasz (Transport, 2008)
The paper refers to some introduction problems of Digital Tachograph System (DTS) in EEA. It affects 25 states of the European Union and EFTA (Island, Liechtenstein, Norway) and Switzerland. The legislation principles and structure of DTS in the EU are characterized, especially Polish elements. The current state of DTS introduction in the EU Member States was also noted. Some problems of data security concern TACHONET system that ensures reliable and secure exchange of data between Member States issuing tachograph cards. The digital tachograph security principles (ITSEC) of the motion sensor, the vehicle unit and the smart cards were taken into consideration.First published online: 27 Oct 2010